On the partial generalization of the measure of transcendence of some formal Laurent series - (:unkn) unknown (My University, 1996)
0

In this work , we determine the transcendence measure of the formal Laurent series "that" whose transcendence lias been established by L.I.Wade. Using the methods and lemmas in P.Bundsclmh's article, measure of the traj.iscenden.ee for .the above... is determined as On the other hand , it was proven that the transcendence series ..... is not a U but is a S or T-number according to the Mahler's classification.
Keywords: Matematik